2015
DOI: 10.1186/s13033-015-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different domains of social capital on psychological distress among Croatian high school students

Abstract: BackgroundSocial capital has been shown to have positive effects on multiple health outcomes among young people (i.e., obesity, diabetes, cardiovascular disease and infectious diseases). Studies are suggesting that social capital is an important asset for the health and wellbeing of children and adolescents, including for their mental health. We sought to examine the influences of different domains of social capital – in the family, in the neighbourhood, and at school – on levels of psychological distress amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…One of the reasons for the association between higher social capital and a better sleep among workers may be due to the barrier effect, where NSC acts as the shock absorber to the stress and strain of the workplace [ 63 , 64 ]. Another possibility is that NSC relieves psychosocial or environmental stresses which disturb the sleep [ 65 ] via the mental wellbeing obtained from mutual trust, reciprocity, wider social networks and social supports [ 66 , 67 ]. Moreover Bassett and Moore [ 10 ] argued that the lower neighborhood trust in a Canadian community increased the likelihood of restless sleep in women and that lower network social capital increased the likelihood of restless sleep in men.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for the association between higher social capital and a better sleep among workers may be due to the barrier effect, where NSC acts as the shock absorber to the stress and strain of the workplace [ 63 , 64 ]. Another possibility is that NSC relieves psychosocial or environmental stresses which disturb the sleep [ 65 ] via the mental wellbeing obtained from mutual trust, reciprocity, wider social networks and social supports [ 66 , 67 ]. Moreover Bassett and Moore [ 10 ] argued that the lower neighborhood trust in a Canadian community increased the likelihood of restless sleep in women and that lower network social capital increased the likelihood of restless sleep in men.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with other studies that measured informal social control with the same question and that also reported no association between informal social control and higher levels of health-related behaviors. 38 , 45 Although informal social control promotes outdoor PA in the neighborhood context by providing a sense of safety, strict maintenance of social order also may be interpreted as a regulation of adolescent behavior. Novak and Kawachi 45 suggest that strict maintenance of social order may have a downside of having too strong SC.…”
Section: Discussionmentioning
confidence: 99%
“…38 , 45 Although informal social control promotes outdoor PA in the neighborhood context by providing a sense of safety, strict maintenance of social order also may be interpreted as a regulation of adolescent behavior. Novak and Kawachi 45 suggest that strict maintenance of social order may have a downside of having too strong SC. For example, restrictions on individual freedom and downward leveling of norms are identified as negative consequences of too strong SC.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30% of children and adolescents present mental disorders in the United States ( Costello et al, 2003 ). In Croatia, the prevalence of mental disorders among youth is 15.7% ( Rudan et al, 2005 ), girls experienced high psychological distress more frequently in the last 30 days, compared with boys (33% vs. 16%) ( Novak & Kawacki, 2015 ). In general, psychological distress is a term frequently used to describe the experience of unpleasant emotions and feelings that influence on everyday functioning ( Perales, del Pozo-Cruz & del Pozo-Cruz, 2014 ) and has been consistently associated with cardiovascular ( Mensah & Collins, 2015 ), metabolic ( Newcomer, 2007 ) and musculoskeletal ( Patten, Williams & Wang, 2006 ) diseases, cancer ( Kisely, Crowe & Lawrence, 2013 ) and overall mortality ( Walker, McGee & Druss, 2015 ).…”
Section: Introductionmentioning
confidence: 99%